Evaluation of the NG-Test Carba 5 for the clinical detection of carbapenemase-producing gram-negative bacteria - Qin, Hai-Feng; He, Jin-Ke; Chen, Xin; Jiang, Ke; Cai, Xiao-Yan; Wu, Xiao-Ni; Ye, Lei; Chen, Hao-Kai; Guo, Xu-Guang; Xia, Yong (Frontiers in Medicine, 2025)
BackgroundCurrently, the spread and prevalence of carbapenem-resistant gram-negative bacteria cause a worldwide health problem, significantly affecting patients’ prognosis. Therefore, reliable detection of carbapenemases is crucial for managing and controlling infections. Numerous investigations have shown that the innovative immunochromatographic assay NG-Test Carba 5 has great sensitivity and specificity for carbapenemase typing. This meta-analysis aimed to comprehensively assess the efficacy of the NG-Test Carba 5 in the clinical detection of carbapenemase-producing gram-negative bacteria.MethodsPreviously published articles were systematically reviewed, relevant data were extracted, and the results were pooled and analyzed using Meta-DiSk 1.4 and Stata 12.0 software.ResultsThe sensitivity, specificity, positive LR value, and negative LR value for the identification of carbapenemase-type KPC, NDM, VIM, IMP, and OXA-48-like by immunochromatographic NG-Test Carba 5 using PCR as gold standard were 0.97 [95% CI (0.97, 0.98)], 0.99 [95% CI (0.99, 1.00)], 65.38 [95% CI (36.73, 116.39)], and 0.03 [95% CI (0.02, 0.05)], respectively, and the combined diagnostic odds ratio was 2,734.42 [95% CI (1,464.05, 5,107.12)]. The AUC of the SROC curve was 0.9976.ConclusionIn summary, the NG-Test Carba 5 is a clinical test that can identify and quickly detect five major carbapenemases, thus offering valuable insights for clinical decision-making and infection control.